EFEKTIVITAS METODE FEAR AROUSING WARNING DALAM MENINGKATKAN INTENSI PELAJAR SEKOLAH DASAR MENYIKAT GIGI DI WAKTU YANG TEPAT: The Effectiveness Of Fear Arousing Warning Method to Increase The Elementary School Students Intention to Brush Teeth at The Right Time - Nuri Sadida; Febrianis Virlita (Journal of Community Mental Health and Public Policy, 2020)
Tooth brushing behavior at the right time (after breakfast and before bed at night) in the province of Jakarta is still low at 3.5%. Proportion of Indonesian children experiencing dental problems aged 5 to 9 years is 28.9%, while those aged 10 to 14 years was 25.2%. This study aims to test the effectiveness of arousing fear warning method in improving the intention of students in elementary school grade IV to brush their teeth at the right time. The study participants were 57 students in the fourth grade from an elementary school (SD) in Jakarta. The type of study was pre-experimental, with a one-group pretest-posttest design, in which one group of students were required to fill the pretest before intervention (arousing fear warning method), and they were asked to fill posttest after the intervention. The dependent variable was measured by Intention of brushingteeth at the right time questionnaire which was designed based on Theory of Planned Behavior (TPB) from Ajzen. The questionnaire consists of 42 item statements using Likert scale. The data was then analyzed using paired samples t-test, and the result showed no significant improvement in posttest scores, which means fear arousing warning method was not effective for improving the intentions of the fourth grade elementary school brushing teeth at the right time.